Adherence to Dihydroartemisinin + Piperaquine Treatment Regimen in Low and High Endemic Areas in Indonesia. (11th March 2022) - Chakim, Irfanul; Pumpaibool, Tepanata; Sayono,; Fauzi, Ekha Rifki
Abstract : After decades of successful artemisinin regimen in combating malaria, its effectiveness has decreased since parasite resistance to the treatment regimen has begun to appear. Adherence to artemisinin combination therapy (ACT) in a population is considered to be the key factor contributing to such resistance phenomenon. Although several studies have tried to demonstrate adherence to several ACT types in a population, only a limited number of studies demonstrated adherence to dihyrdroartemisinin + piperaquine (DHP) regimen. The present study was conducted in two localities representing low and high endemic areas in Indonesia. Active case detection (ACD) and passive case detection (PCD) have been applied to screen for malaria case in the localities. At day 3, patients were visited in the house to be interviewed using structured questionnaire. Capillary sample of each patient was also collected on Whatman® filter paper at day 60 to observe the piperaquine metabolite of the patients. 47 and 91 (out of 62 and 138) patients from Jambi and Sumba, respectively, were successfully enrolled in this study. In Jambi, the level of adherence was 66%, while that in Sumba was 79.1%. The associated factors of adherence in our study settings are patient age group (OR = 1.65 [CI: 0.73–3.73]) and patients' knowledge of malaria prevention measure (OR = 0.29 [CI: 0.09–0.9]). Our study suggested that the adherence to ACT medication among population in our study setting is considered to be less than 80%, which needs to be elevated to avoid the growing trend of treatment failure as seen globally. Additionally, our study found that metabolite at day 60 after prescription of piperaquine could be a potential marker for monitoring adherence to piperaquine drug in a population.